Hair cortisol concentrations in higher‐ and lower‐stress mother–daughter dyads: A pilot study of associations and moderators. Issue 5 (28th March 2015) - Ouellette, Sarah J.; Russell, Evan; Kryski, Katie R.; Sheikh, Haroon I.; Singh, Shiva M.; Koren, Gideon; Hayden, Elizabeth P.
ABSTRACT Hair cortisol concentrations (HCC) are receiving increased attention as a novel biomarker of psychophysiological responses to chronic stress, with potential relevance for psychopathology risk research. We examined the validity of HCC as a marker of psychosocial stress in mother (Mage = 37.87 years)–daughter (Mage = 7.62 years) dyads characterized by higher (n = 30) or lower (n = 30) maternal chronic stress. Additionally, we examined whether early care moderated similarity of HCC levels within dyads. Higher‐stress mothers had significantly lower HCC compared to lower‐stress mothers, consistent with other research showing that chronic stress leads to blunted HPA axis activity over time. Further, HCC in daughters were significantly and positively associated with previously assessed salivary cortisol stress reactivity. Finally, mother–daughter HCC associations were significantly moderated by negative parenting styles, such that associations became stronger as quality of parenting decreased. Findings overall indicate that HCC may be a useful marker of cortisol responses to chronic stress. © 2015 Wiley Periodicals, Inc. Dev Psychobiol 57: 519–534, 2015.